Neglected disease in mentally ill patients: Major tuberculosis outbreak in a psychiatric hospital - Zmak, Ljiljana; Obrovac, Mihaela; Lovric, Zvjezdana; Jankovic Makek, Mateja; Katalinic Jankovic, Vera (American journal of infection control, 2017)
•Mentally ill patients are at increased risk of tuberculosis.•Maintaining awareness of tuberculosis in psychiatric patients is necessary to avoid diagnostic delay.•Active approach is necessary in adopting infection control measures in psychiatric institutions. As tuberculosis incidence decreases, the possibility of overlooking the disease increases, especially in vulnerable populations. We describe here a major tuberculosis outbreak among mentally ill patients in Croatia, focusing on 1 regional hospital where most patients were hospitalized. The outbreak emphasizes the vulnerability of mentally ill patients to tuberculosis infection and the complexity of infection control measures in psychiatric institutions. The awareness of tuberculosis in these settings should be maintained to interrupt prolonged exposure and avoid unnecessary infection.